ответ: у = 39
30 + 40 : (y - 37) = 50
40 : (y - 37) = 20
у - 37 = 2
у = 39
Пошаговое объяснение:
ответ:и так, решение:
30 + 40 : (у - 37) = 50
40 : (у - 37) = 50 - 30
40 : (у - 37) = 20
у - 37 = 40 : 20
у = 2 + 37
Проверка: 30 + 40 : (39 - 37) = 50
30 + 40 : 2 = 50
30 + 20 = 50
50 = 50
ответ: у = 39
30 + 40 : (y - 37) = 50
40 : (y - 37) = 20
у - 37 = 2
у = 39
Пошаговое объяснение:
ответ:и так, решение:
Пошаговое объяснение:
30 + 40 : (у - 37) = 50
40 : (у - 37) = 50 - 30
40 : (у - 37) = 20
у - 37 = 40 : 20
у - 37 = 2
у = 2 + 37
у = 39
Проверка: 30 + 40 : (39 - 37) = 50
30 + 40 : 2 = 50
30 + 20 = 50
50 = 50